Folliculitis Decalvans and Pyoderma Gangrenosum - Rajbhandari, Sudarshan L; Jagat, SP (Medical Journal of Shree Birendra Hospital, 2005)
Folliculitis decalvans is a rare chronic progressive follicular pustular eruption that results in cicatricial alopecia of scalp and other areas.